New Challenges Require New Solutions. Book review of ‘The Soft Power of the United Kingdom’ by E.M. Kharitonova - N. V. Yudin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a new monograph ‘The Soft Power of the United Kingdom’ by Elena M. Kharitonova, published by the Primakov National Research Institute of World Economy and International relations (IMEMO) of the Russian Academy of Sciences. The reviewer emphasizes that a distinguishing advantage of this book over many contemporary Russian and foreign scholarly works on soft power is its special focus on both theoretical aspects of soft power policies and the bibliography of this phenomenon. The reviewer considers this approach especially relevant given the fact that it is impossible to fully comprehend the essence of Joseph Nye’s ideas without a clear understanding of the role of soft power concept in the studies of power in international relations. The review examines each of three chapters of the book, outlines strengths and weaknesses of the author’s position. For instance, the reviewer points to a somewhat descriptive (rather than analytical) character of certain book sections and at times excessively uncritical treatment of public statements. However, the reviewer stresses that these shortcomings do not in any way downplay the merits of the book, which stands out as a novel, comprehensive, and highly relevant piece of research carried out with great professionalism. The book examines, summarizes and structures a significant amount of data from various sources (the Parliament documentation, the UK political parties’ manifestos, media reports, surveys of public opinion and soft power indexes). In that regard the book under review not only yields a significant contribution to studies on the role of soft power in the foreign policy of the United Kingdom but may also serve aa a good basis for the formulation of practical recommendations for both improving RussianBritish contacts (for example in science diplomacy) and developing the Russian approaches to ‘soft power’.